2015
DOI: 10.3390/pharmaceutics7030255
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Biological Proteins for Liver Failure Therapy

Abstract: Biological proteins have unlimited potential for use as pharmaceutical products due to their various biological activities, which include non-toxicity, biocompatibility, and biodegradability. Recent scientific advances allow for the development of novel innovative protein-based products that draw on the quality of their innate biological activities. Some of them hold promising potential for novel therapeutic agents/devices for addressing hepatic diseases such as hepatitis, fibrosis, and hepatocarcinomas. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 119 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Liver failure is a heterogeneous and serious disease that is characterized by major harms, treatment difficulties, poor prognosis, and high mortality. 26,27 Liver failure can be categorized into acute liver failure, subacute liver failure, ACLF, and chronic liver failure; ACLF is the most common. 28 HBV-ACLF can lead to metabolic disorders and further impairment of multiple organ functions.…”
Section: Discussionmentioning
confidence: 99%
“…Liver failure is a heterogeneous and serious disease that is characterized by major harms, treatment difficulties, poor prognosis, and high mortality. 26,27 Liver failure can be categorized into acute liver failure, subacute liver failure, ACLF, and chronic liver failure; ACLF is the most common. 28 HBV-ACLF can lead to metabolic disorders and further impairment of multiple organ functions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed to date dealing with this subject have shown that many tissues produce and locally release erythropoietin in response to hypoxic, biochemical and physical stress. Erythropoietin protects tissue from ischemia and reperfusion injury, it has antiapoptotic eff ect and promotes tissue regeneration [11][12][13][14]32 . We also used erythropoietin to predict whether the patient would be assigned to group 2 according to ISS score.…”
Section: Epo = Erythropoietinmentioning
confidence: 99%
“…As of today, many prognostic factors have been developed 5 . Erythropoietin, a glycoprotein predominantly synthesized in the kidneys, plays the central role in stimulation of erythropoiesis, but also has other purposes, such as cytoprotective, anti-apoptotic, anti-infl ammatory and antioxidant activity 11,12 . Studies have shown that the administration of erythropoietin before or after stressful event that led to cell ischemia protects cells from development of ischemic sequels 13 .…”
Section: Introductionmentioning
confidence: 99%
“…13% cationic lysine and arginine amino acids, and ca. 11% hydrophobic leucine, isoleucine, methionine, and valine), and gelatin-based matrices can in principle be used to deliver both small molecules and macromolecules. In this study, we focus on a selection of low-molecular-weight drugs used in the clinic, as depicted in Figure .…”
Section: Introductionmentioning
confidence: 99%